An Unusual Neck Mass: A Case of a Parathyroid Cyst and Review of the Literature - Anand Goomany; Amy Rafferty; Ian Smith (Case Reports in Surgery)
Parathyroid cysts (PC) are an unusual cause of neck swellings. The majority are nonfunctioning and prove to be a diagnostic challenge given their nonspecific physical and radiological characteristics. This is compounded by their rare occurrence, leading them to be overlooked in the differential diagnosis of neck lumps. Imaging techniques fail to determine the origin of these lesions, but a preoperative diagnosis can be achieved by fine-needle aspiration and measurement of cystic fluid C-terminal parathyroid hormone levels. Treatment of nonfunctioning cysts remains controversial and includes needle aspiration, injection of sclerosant, or surgical excision. We present a case of a 44-year-old female presenting with an asymptomatic anterior neck swelling, diagnosed postoperatively as a parathyroid cyst.